2018
DOI: 10.4034/pboci.2018.181.86
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Among Kosovar Children with Type 1 Diabetes Mellitus

Abstract: Objective: To evaluate the oral health status in children with type 1 diabetes mellitus. Material and Methods: Dental examinations, based on World Health Organization caries diagnostic criteria for DMFT index for permanent dentition and survey were performed among 160 children, aged 10-15-year-old, divided into two groups. The first group consisted of 80 children with type 1 diabetes mellitus (41 females, 39 males), and in the second group, consisted 80 healthy children (49 females, 31 males). Frequency, odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 , 33 – 35 ]. Previously conducted studies in Kosovo compared the oral health of children with diabetes and control groups [ 12 , 36 , 37 ], whereas our study goes deeper and reveals the impact of metabolic control on oral health among children with diabetes. Many studies have shown that one of the most evident oral symptoms of diabetes is a reduction in the salivary flow rate.…”
Section: Discussionmentioning
confidence: 57%